Cronobiological and sleep related aspects associated to Neurodevelopment and academic performance in pediatric age - Meira e Cruz, Miguel (2021)
Biological rhythms and sleep as their main representative are relevant biofunctional factors to the neuro-cognitive and behavioral development with particular interest in pediatric domain. Some aspects associated to central nervous system and higher function homeostasis, like social-afective equilibrium, critical judgement and memories consolidations and learning, have, in this phase of life, a relationship with the circadian timing system stability and with cronotype. On the other hand, inadequate or insufficient sleep has a negative impact in several biopsychosocial parameters interacting with these domains and conditioning the normal development causing changes in neuro-cognitive and behavioral performance. This review looked for the fundamental aspects of chronobiology and sleep physiology applied to neurodevelopment and its impact in the educational context regarding academic performance.